2014
DOI: 10.1063/1.4893362
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of stability and diffusion mechanisms of impurity atoms in Ge crystals

Abstract: Ge-based substrates are being developed for applications in advanced nano-electronic devices because of their higher intrinsic carrier mobility than Si. The stability and diffusion mechanism of impurity atoms in Ge are not well known in contrast to those of Si. Systematic studies of the stable sites of 2nd to 6th row element impurity atoms in Ge crystal were undertaken with density functional theory (DFT) and compared with those in Si crystal. It was found that most of the impurity atoms in Ge were stable at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…Obviously, no review can consider all the references related to such a technological issue and many key contributions have not been discussed (for example, References [114][115][116][117][118][119][120]). Additionally, from an experimental viewpoint, the diffusion and activation of dopants can be further complicated by parameters such as the thermal budget, particularly when considering non-equilibrium techniques (e.g., laser, flash, and microwave annealing) [121,122].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, no review can consider all the references related to such a technological issue and many key contributions have not been discussed (for example, References [114][115][116][117][118][119][120]). Additionally, from an experimental viewpoint, the diffusion and activation of dopants can be further complicated by parameters such as the thermal budget, particularly when considering non-equilibrium techniques (e.g., laser, flash, and microwave annealing) [121,122].…”
Section: Discussionmentioning
confidence: 99%
“…Such sites are indeed experimentally observed for O and N. , When the latter lower-symmetry sites are explicitly simulated, both elements strongly prefer an interstitial site, twofold-coordinated for O and trifold-coordinated for N, as well as a distorted substitutional site. Maeta and Sueoka examined the twofold-coordinated site for larger elements also but found that it quickly becomes enthalpically unfavorable . The remaining TV positions in Ge consist of transition metals, which are capable of increased interactions through their incomplete d shells.…”
Section: Resultsmentioning
confidence: 99%
“…While Si has been the focus of the semiconductor industry for the last 50 years, Ge has recently regained interest as a high-mobility substrate and is still commonly used in niche markets such as radiation detectors and space solar cells. Impurities are essential to both materials, providing control over the semiconductor’s properties during production and device operation. Knowledge of impurity properties in Ge is significantly less complete than for Si, and even for the latter only a subset of the periodic table has been studied. , Through high-throughput screening this knowledge can be considerably extended beyond what is currently experimentally known. In this way a complete and consistent data set can be provided for both materials and used to gain insights into future experimental and theoretical research as well as industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The formation energies of sphalerite solid solutions (E FE , [12,14]) were obtained using the calculated total energies. We considered the following models: two In atoms substitute for two Zn atoms in ZnS crystal structure; two In atoms substitute for two Zn atoms in ZnS crystal structure with the formation of a vacancy at Zn position; one In and one Cu atom substitute for two Zn atoms in ZnS crystal structure.…”
Section: Density Functional Theory (Dft) Calculationsmentioning
confidence: 99%